Using Innovation-Corps (I-Corps™) Methods to Adapt a Mobile Health (mHealth) Obesity Treatment for Community Mental Health Settings - Haddad, Rita; Badke D'Andrea, Carolina; Ricchio, Amanda; Evanoff, Bradley; Morrato, Elaine H.; Parks, Joseph; Newcomer, John W.; Nicol, Ginger E. (Frontiers in Digital Health, 2022)
Background: We employed Innovation Corps (I-Corps™) methods to adaptation of a mobile health (mHealth) short-message-system (SMS) -based interactive obesity treatment approach (iOTA) for adults with severe mental illness receiving care in community settings. Methods: We hypothesized “jobs to be done” in three broad stakeholder groups: "decision makers" (DM = state and community clinic administrators), "clinician consumers" (CC = case managers, peer supports, nurses, prescribers) and “service consumers” (SC = patients, peers and family members). Semistructured interviews (N=29) were recorded and transcribed ver batim and coded based on pragmatic-variant grounded theory methods. Results: Four themes emerged across groups: education, inertia, resources and ownership. Sub-themes in education and ownership differed between DM and CC groups on implementation ownership, intersecting with professional development, suggesting the importance of training and supervision in scalability. Sub-themes in resources and inertia differed between CC and SC groups, suggesting illness severity and access to healthy food as major barriers to engagement, whereas the SC group identified the need for enhanced emotional support, in addition to pragmatic skills like menu planning and cooking, to promote health behavior change. Although SMS was perceived as a viable education and support tool, CC and DM groups had limited familiarity with use in clinical care delivery. Conclusions: Based on customer discovery, the characteristics of a minimum viable iOTA for implementation, scalability and sustainability include population- and context-specific adaptations to treatment content, interventionist training and delivery mechanism. Successful implementation of an SMS-based intervention will likely require micro-adaptations to fit specific clinical settings.